ANALISIS PUTUSAN HAKIM NOMOR 1642/Pdt.G/2020/PA.JP DALAM PEMBAGIAN HARTA WARIS ANTARA ANAK LAKI-LAKI DAN PEREMPUAN - Muhamad Hasan Sebyar & Purnama Hidayah Harahap (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This study aims to analyze the decision of the West Jakarta Religious Court judge Number 1642 / Pdt.G / 2020 / PA.JP in the case of a lawsuit on inheritance from the perspective of Qawaid Fiqiyyah. This study uses three approaches, namely a legal approach, a historical approach and a conceptual approach. The results of this study indicate that the legal reasoning used by judges in deciding 1: 1 inheritance between boys and girls is very weak. The distribution of inheritance is not only based on how much he does, but rather on the roles and obligations assumed by each. If boys want the distribution of inheritance to be divided according to Islam, then the judge should decide according to Islamic law للذكر مثل حظ األنثيين, which is 2: 1